2017
DOI: 10.1021/acsomega.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive Response of Quasi-One-Dimensional ZnO Nanowires Using an in Situ Electromechanical Device

Abstract: Quasi-one-dimensional structures from metal oxides have shown remarkable potentials with regard to their applicability in advanced technologies ranging from ultraresponsive nanoelectronic devices to advanced healthcare tools. Particularly due to the piezoresistive effects, zinc oxide (ZnO)-based nanowires showed outstanding performance in a large number of applications, including energy harvesting, flexible electronics, smart sensors, etc. In the present work, we demonstrate the versatile crystal engineering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…However, as it was demonstrated later using time-dependent electromechanical measurements, the increased apparent piezoresistive coefficients were actually due to charge trapping and detrapping on the surface of depleted Si, whereas the intrinsic piezoresistvity of the nanostructured material is essentially the same as that of bulk (Milne et al, 2010). Recent studies on semiconducting metal oxide thin films and nanostructures, e.g., on TiO 2 (Fraga et al, 2012), MoO 3 (Wen et al, 2014), and ZnO (Kaps et al, 2017); as well as on layered transition metal dichalcogenides, e.g., MoS 2 (Nayak et al, 2014;Manzeli et al, 2015), MoSe 2 , WSe 2 (Hosseini et al, 2015), and PtSe 2 (Li et al, 2016;Wagner et al, 2018) showed highly strain dependent electronic properties, giving rise to quite high GFs comparable to those of Si and Ge (e.g. 441 for MoO 3 nanobelts, −148 for MoS 2 monolayers or −85 for PtSe 2 thin films).…”
Section: Introductionmentioning
confidence: 86%
“…However, as it was demonstrated later using time-dependent electromechanical measurements, the increased apparent piezoresistive coefficients were actually due to charge trapping and detrapping on the surface of depleted Si, whereas the intrinsic piezoresistvity of the nanostructured material is essentially the same as that of bulk (Milne et al, 2010). Recent studies on semiconducting metal oxide thin films and nanostructures, e.g., on TiO 2 (Fraga et al, 2012), MoO 3 (Wen et al, 2014), and ZnO (Kaps et al, 2017); as well as on layered transition metal dichalcogenides, e.g., MoS 2 (Nayak et al, 2014;Manzeli et al, 2015), MoSe 2 , WSe 2 (Hosseini et al, 2015), and PtSe 2 (Li et al, 2016;Wagner et al, 2018) showed highly strain dependent electronic properties, giving rise to quite high GFs comparable to those of Si and Ge (e.g. 441 for MoO 3 nanobelts, −148 for MoS 2 monolayers or −85 for PtSe 2 thin films).…”
Section: Introductionmentioning
confidence: 86%
“…Potential applications of ZnO materials include optical waveguides [17], varistors [18], solid-state lighting [19], gas sensors [20], and transparent conductive films. Because of its wide band gap, ZnO is a promising candidate material for use in solid-state optoelectronics that emit in the blue or ultraviolet (UV) spectral range, including lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a perfect control over the quality of ZnO nanomaterial produced is essential to build a high performance electronic device. Different bottom-up growth techniques, including flame transport approach [15][16][17][18], vaporliquid-solid (VLS) [19], electrochemical deposition [20], hydrothermal and/or chemical bath deposition [11,[21][22][23][24] have been utilized for the synthesis of 1D ZnO NWs. Nevertheless, most of the techniques are limited by their high temperature process that cannot be scaled up over large device area at very low cost, on plastic substrates for example.…”
Section: Introductionmentioning
confidence: 99%